2012
DOI: 10.1111/j.1524-475x.2012.00766.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between skin stretching/contraction and pathologic scarring: The important role of mechanical forces in keloid generation

Abstract: Keloids tend to occur on highly mobile sites with high tension. This study was designed to determine whether body surface areas exposed to large strain during normal activities correlate with areas that show high rates of keloid generation after wounding. Eight adult Japanese volunteers were enrolled to study the skin stretching/contraction rates of nine different body sites. Skin stretching/contraction was measured by marking eight points on each region and measuring the change in location of the marked point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
203
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(213 citation statements)
references
References 31 publications
7
203
2
1
Order By: Relevance
“…Consistent with this, it has been shown that mechanical forces can induce formation of scars (10) and keloid (11). It has long been known that skin sites that are exposed to high stretch and contraction, show enhanced susceptibility to develop keloid disease (11). This underlines the importance of mechanosensitive cell-ECM crosstalk in this disease and underscores the significance of the study of Harn et al (4).…”
Section: Accepted For Publication 6 May 2015supporting
confidence: 63%
“…Consistent with this, it has been shown that mechanical forces can induce formation of scars (10) and keloid (11). It has long been known that skin sites that are exposed to high stretch and contraction, show enhanced susceptibility to develop keloid disease (11). This underlines the importance of mechanosensitive cell-ECM crosstalk in this disease and underscores the significance of the study of Harn et al (4).…”
Section: Accepted For Publication 6 May 2015supporting
confidence: 63%
“…Both skin and scar tissue structurally adapt to loading, exhibiting rapid parallel realignment of collagen in response to stretch. 17 Additionally, clinical and preclinical data demonstrate pronounced scarring in anatomical areas with high tissue tension, [18][19][20] thereby indicating that the wound environment's biomechanics can greatly influence healing outcomes. Significantly reducing tension in healing wounds could act to minimize scarring, as was recently demonstrated by using a force-modulating polymer wound dressing.…”
Section: Effect Of Scarringmentioning
confidence: 99%
“…(b) Generally keloids tend to occur on highly mobile sites with high tension such as shoulders, neck, and presternum [26,27]. (c) There are familial patterns of keloid distribution [11].…”
Section: Anatomical Sitementioning
confidence: 99%